CUSTOMER JOURNEY MAPPING ANALYSIS TO IMPROVE CUSTOMER EXPERIENCE AND CUSTOMER SATISFACTION IN BANK BJB MEDAN BRANCH SERVICES - Afifah Riadi Putri; Doli Muhammad Jafar Dalimunthe; Muhammad Anggia Muchtar (Program Pascasarjana UIN Sumatera Utara, 2025)
This study aims to examine and analyze: (1) the effect of Customer Journey Mapping on Customer Experience, (2) the effect of Customer Experience on Customer Satisfaction, (3) the effect of Customer Journey Mapping on Customer Satisfaction, and (4) the indirect effect of Customer Journey Mapping through Customer Experience on Customer Satisfaction in the services of bank bjb Medan Branch. This research employs a quantitative approach with a survey method by distributing questionnaires to walk-in customers of bank bjb Medan Branch. The population in this study consists of 1,868 customers, and based on the Raosoft sample size formula, a total of 319 respondents were selected as the final sample. The data were analyzed using the Structural Equation Modeling (SEM) technique with the SmartPLS software. The results indicate that Customer Journey Mapping has a significant effect on both Customer Experience and Customer Satisfaction, either directly or indirectly through Customer Experience. These findings suggest that optimizing each stage of the customer journey can enhance both Customer Experience and satisfaction with the services of bank bjb Medan Branch.